2015
DOI: 10.1108/arla-08-2014-0113
|View full text |Cite
|
Sign up to set email alerts
|

The role of information technology in the environmental performance of the firm

Abstract: Purpose The purpose of this paper is to explore the role of information technologies (IT) in the impact of environmental practices on environmental performance. Design/methodology/approach The authors use data from the fifth (2009) round of the International Manufacturing Strategy Survey (IMSS) which includes responses from manufacturing plants within the manufacturing industry in Brazil, China, Germany, Hungary and USA. The authors use mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
3
9
1
1
Order By: Relevance
“…Our results say that the Cluster 1 companies using ICT on a more advanced level have significantly better environmental performance in 11 out of 17 dimensions. The results correspond with the results of Melville (2010) and Gimenez et al (2015) who emphasize that ICT tools can enable organizational practices and processes that improve environmental and economic performance. We also found that it is worth to interpret environmental performance in a wider sense, and add input, outcome and strategic dimensions to process and output-oriented indicators (Schultze & Trommer, 2012;Butti et al, 2019;Gaviglio et al, 2017).…”
Section: Studies and Articlessupporting
confidence: 88%
See 2 more Smart Citations
“…Our results say that the Cluster 1 companies using ICT on a more advanced level have significantly better environmental performance in 11 out of 17 dimensions. The results correspond with the results of Melville (2010) and Gimenez et al (2015) who emphasize that ICT tools can enable organizational practices and processes that improve environmental and economic performance. We also found that it is worth to interpret environmental performance in a wider sense, and add input, outcome and strategic dimensions to process and output-oriented indicators (Schultze & Trommer, 2012;Butti et al, 2019;Gaviglio et al, 2017).…”
Section: Studies and Articlessupporting
confidence: 88%
“…In the paper, we analyzed the level of ICT use and the environmental performance of companies based on two theoretical models. Some previous scientific papers already connected ICT and environmental sustainability before (Ishida, 2015;Ollo-Lopez & Aramendía-Muneta, 2011;Yi & Thomas, 2007;Gimenez et al, 2015), but either they used a technology-oriented ICT approach (Becker et al, 2009;Weber & Kauffman, 2011;Gimenez et al, 2015) or interpreted sustainability only through output/processbased indicators (Ishida, 2015;Higón et al, 2017;Gimenez et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees gainedmotivation when their performance waslinked with rewards such as promotion, fringe benefits, flexible working hours, bonuses, etc. [48] reported a positive and significant relationship between green rewards and sustainable performance. Similarly, [49] also reported a positive and significant association between green rewards and sustainable performance.…”
Section: Green Rewardsmentioning
confidence: 96%
“…These seminal studies, although lacking a contrasted theoretical base to support the theses, had a strong impact on management decisions about investing in this technology. Over the years, papers have provided empirical support for the strategic nature of IT (Gimenez et al , 2015; Moliner-Velázquez et al , 2015; Sirirak et al , 2011). This study makes a contribution in this direction by justifying that, both directly and indirectly, IT use positively influences management innovation.…”
Section: Introductionmentioning
confidence: 99%